Indonesia : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report, 2005)
This report on the Observance of Standards and Codes on Data Module for Indonesia highlights that the Indonesian statistical system is undergoing fundamental transition. The statistical agencies are dealing with important challenges. They are at various stages of adopting and implementing internationally recognized best practice methodologies for each major macroeconomic dataset. They are also seeking to adapt the statistical system to measure ongoing structural change in the economy, including increasing global integration.